2018
DOI: 10.1097/olq.0000000000000752
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Geosexual Archetypes: Mapping the Sexual Travels and Egocentric Sexual Networks of Gay and Bisexual Men in Toronto, Canada

Abstract: Six geosexual archetypes were identified: hosters, house-callers, rovers, privates, travellers, and geoflexibles, each with different characteristic profiles. Prioritizing interventions to hosters, rovers, and geoflexibles may reduce sexually transmitted infection transmission.Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Different groups of people may interact with these apps [49], and the places that people interact may also be more diverse. These changes likely alter the geography of sexual networks and HIV transmission potential [50]. Past research has suggested that MSM using geo-social apps had higher rates of drug and alcohol use, and higher sexual behaviors implying HIV transmission compared with non-app using MSM [51].…”
Section: Discussionmentioning
confidence: 99%
“…Different groups of people may interact with these apps [49], and the places that people interact may also be more diverse. These changes likely alter the geography of sexual networks and HIV transmission potential [50]. Past research has suggested that MSM using geo-social apps had higher rates of drug and alcohol use, and higher sexual behaviors implying HIV transmission compared with non-app using MSM [51].…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the sensitivity of jurisdictional variations in access to PrEP by implementing scenarios that used the national PrEP coverage for every jurisdiction and jurisdiction-speci c PrEP coverage. To test the sensitivity of jurisdictional-mixing, we evaluated scenarios with varying levels of mixing, using data from behavioral surveys and phylogenetic studies [20][21][22][23][24][25] to set the range of values. We discuss these scenarios under Scenarios modeled.…”
Section: Compartmental Modelmentioning
confidence: 99%
“…Another survey presented in study [21] about young black MSM between ages 16 to 24, states that 20% of the cases reported travelling to another region or outside the state of Mississippi. Study [24] which conducted interviews with MSM from Toronto, Canada, states that 30% of the study's participants had sex with partners outside of their town. Study of phylogenetic analysis of HIV sequences in Shanghai [23] states that 33.8% of the HIV sequences analyzed were associated to infected individuals from another province.…”
Section: Jurisdictional-mixing Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations